2011
DOI: 10.3989/scimar.2011.75n3605
|View full text |Cite
|
Sign up to set email alerts
|

Larval fish assemblages in coastal waters of central Greece: reflections of topographic and oceanographic heterogeneity

Abstract: SUMMARY: Patterns in the mesoscale distribution of larval fish in the coastal waters of central Greece, an area of high topographic and bathymetric complexity, were analysed using samples collected during two ichthyoplankton surveys in July 1998 and June 1999. Salinities were lower in the eastern (Aegean) part of the study area due to the influence of waters originating from the Black Sea. In this region, larvae of many epipelagic and benthopelagic (typically summer spawning) species were less abundant in June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This fact may explain the broad distribution of bullet tuna larvae over the study area, since most of the bullet tuna positive stations were located over the Gulf of Gabes continental shelf, which is the widest part of the Mediterranean Sea (Burollet, 1979). Atlantic black skipjack larvae were considerably less abundant than bullet tuna in our samples, as also reported in other ichthyoplankton studies in the Mediterranean Sea (Garcia et al 2005b;Alemany et al 2010;Somarakis et al 2002;2011a). The confinement of Atlantic black skipjack larvae to the stations located between Kerkennah and Djerba Island which are characterized by low depths, may indicate that the spawners of the species tend to avoid open sea waters, showing a preference for stations over the continental shelf.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This fact may explain the broad distribution of bullet tuna larvae over the study area, since most of the bullet tuna positive stations were located over the Gulf of Gabes continental shelf, which is the widest part of the Mediterranean Sea (Burollet, 1979). Atlantic black skipjack larvae were considerably less abundant than bullet tuna in our samples, as also reported in other ichthyoplankton studies in the Mediterranean Sea (Garcia et al 2005b;Alemany et al 2010;Somarakis et al 2002;2011a). The confinement of Atlantic black skipjack larvae to the stations located between Kerkennah and Djerba Island which are characterized by low depths, may indicate that the spawners of the species tend to avoid open sea waters, showing a preference for stations over the continental shelf.…”
Section: Discussionsupporting
confidence: 66%
“…Mar. Sci., 14/1, 2013, 5-14 rhenian coastal waters (Cavallaro et al 1997;Piccinetti et al 1997), in the Ionian (Santamaria et al 1996(Santamaria et al , 2000Somarakis et al 2011a) and Levantine Kahraman & Alicli, 2007) Seas and in the Aegean Sea (Somarakis et al 2002;Isari et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat-wise, the proportion of pelagic adult species was 61.1% epipelagic, 22.2% mesopelagic 11.1% and benthic 38.9%. (Somarakis et al, 2011) reported that in coastal waters of central Greece identified groups of the stations dominated by larvae of epipelagic, bentopelagic and mesopelagic species. Mesopelagic species also have a very low economic value, nevertheless, their abundance in the Mediterranean sea makes them the best-represented member of the deep water fauna they are the most common prey to other fish species (Olivar et al, 1998;Somarakis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, metamorphosis together with predation, that causes diff erential larval mortality between species within the assemblage, are the main factors leading to assemblage disruptions (Miller, 2002). Several studies have described the composition and spatio-temporal variation of larval fi sh assemblages, particularly in the Mediterranean Sea (Olivar et al, 2010;Somarakis et al, 2011a) and in the Canaries system (Moyano et al, 2009(Moyano et al, , 2014. On the Moroccan Atlantic coast, previous studies have focused on the horizontal eggs and larvae distribution of small pelagic fi shes (Ettahiri, 1996;Berraho, 2007).…”
Section: Introductionmentioning
confidence: 98%